Scaffold Diversity Synthesis and Its Application in Probe and Drug Discovery. Issue 27 (17th May 2016) - Garcia‐Castro, Miguel; Zimmermann, Stefan; Sankar, Muthukumar G.; Kumar, Kamal
Abstract: Scaffold diversity is a crucial feature of compound collections that has a huge impact on their success in biological screenings. The synthesis of highly complex and diverse scaffolds, which could be based on natural products, for example, is an arduous task that requires expertise in various aspects of organic synthesis and structural analysis. This challenge has been addressed by a number of synthesis designs, which employ natural products as a source of scaffold diversity, transform suitably designed common intermediates into various molecular frameworks, or entail highly concise synthetic routes to a number of distinct and complex scaffolds. In this Minireview, we highlight recent synthetic developments towards the construction of diverse and complex scaffolds and the application of the resulting compound collections in drug and probe discovery. Abstract : Complexity and diversity : The synthesis of compound libraries with a high degree of scaffold diversity has been addressed by transforming suitable common intermediates into various molecular frameworks or by using natural products as a source of scaffold diversity. In this Minireview, recent developments towards the construction of such libraries and their application in drug and probe discovery are summarized.